Deletion of Mitochondrial Porin Alleviates Stress Sensitivity in the Yeast Model of Shwachman-Diamond Syndrome. Issue 12 (20th December 2015) - Kanprasoet, Waruenada; Jensen, Laran T.; Sriprach, Suwimon; Thitiananpakorn, Kanate; Rattanapornsompong, Khanti; Jensen, Amornrat Naranuntarat
Abstract: Shwachman-Diamond syndrome (SDS) is a multi-system disorder characterized by bone marrow failure, pancreatic insufficiency, skeletal abnormalities, and increased risk of leukemic transformation. Most patients with SDS contain mutations in the Shwachman-Bodian-Diamond syndrome gene ( SBDS ), encoding a highly conserved protein that has been implicated in ribosome biogenesis. Emerging evidence also suggests a distinct role of SBDS beyond protein translation. Using the yeast model of SDS, we examined the underlying mechanisms that cause cells lacking Sdo1p, the yeast SBDS ortholog, to exhibit reduced tolerance to various stress conditions. Our analysis indicates that the environmental stress response (ESR), heat shock response (HSR), and endoplasmic reticulum unfolded protein response (UPR) of sdo1 Δ cells are functional and that defects in these pathways do not produce the phenotypes observed in sdo1 Δ yeast. Depletion of mitochondrial DNA (mtDNA) was observed in sdo1 Δ cells, and this is a probable cause of the mitochondrial insufficiency in SDS. Prior disruption of POR1, encoding the mitochondrial voltage dependent anion channel (VDAC), abrogated the effects of SDO1 deletion and substantially restored resistance to environmental stressors and protected against damage to mtDNA. Conversely, wild-type cells over-expressing POR1 exhibited growth impairment and increased stress sensitivity similar to that seen in sdo1 Δ cells. Overall, our results suggest that specific VDAC inhibitors may have therapeutic benefits for SDS patients.